Learning to Live: Six Essays on Marcel Proust - Ferraris, Maurizio, (Value Inquiry Book Series ;, 2020)
In this collection of essays, Maurizio Ferraris explores the world portrayed in Marcel Proust's In Search of Lost Time. He ponders how memory is tied to self-identification and knowledge; how the passage of time is only perceptible after it has passed; and how life, ultimately, is accurately portrayed in literature in ways that were seen as inconceivable in our youth. Running throughout the book is the sense that memory is all we are; we are what we remember or what others remember of us.